Illusory Feature Slowing: Evidence for Perceptual Models of Global Facial Change. (April 2015) - Cook, Richard; Aichelburg, Clarisse; Johnston, Alan
Upright static faces are widely thought to recruit holistic representations, whereby individual features are integrated into nondecomposable wholes for recognition and interpretation. In contrast, little is known about the perceptual integration of dynamic features when viewing moving faces. People are frequently exposed to correlated eye and mouth movements, such as the characteristic changes that accompany facial emotion, yawning, sneezing, and laughter. However, it is unclear whether the visual system is sensitive to these dynamic regularities, encoding facial behavior relative to a set of dynamic global prototypes, or whether it simply forms piecemeal descriptions of feature states over time. To address this question, we sought evidence of perceptual interactions between dynamic facial features. Crucially, we found illusory slowing of feature motion in the presence of another moving feature, but it was limited to upright faces and particular relative-phase relationships. Perceptual interactions between dynamic features suggest that local changes are integrated into models of global facial change.